"Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Pendidikan Kewarganegaraan " - Hidayah, Fathul (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the effect of the Discovery Learning learningmodel using video media on the learning outcomes of fifth grade elementary schoolstudents. This type of research is quantitative research in the form of Pre-ExperimentalDesign with the type of One Group Pretest-Posttest. The population of this study was thefifth grade students of SD N Adipuro. The sample used in this study was the fifth gradestudents of SD N Adipuro which consisted of 40 students using the collected samplingtechnique. In collecting data using observation techniques, and interviews Based on theresults of the study, it is known that the learning outcomes of grade 5 students haveincreased through the application of discovery learning strategies. Through the discoverylearning model, the students are more enthusiastic in participating in learning. So, basedon the results of the research analysis conducted, it can be concluded that there is aninfluence of the Discovery Learning model using video media on the learning outcomes offifth grade students at SDN Adipuro..